Penyimpanan Data Obat dalam Human Machine Interface pada Vertical Carousel Obat - Irwanto Zarma Putra; Dessy Oktani; Widya Rika Puspita; Selvi Fitri Yani; Naufal Shadiq Maulana (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2023)
Pharmacies are one of the health facilities that have spread widely in Indonesia, with medicines being one of the needs in the health world. However, conventional storage with so many types of medicines is one of the factors when pharmacists are looking for drugs that require less time efficiently. To help with this problem, you can use a vertical carousel storage machine using real-time storage by utilizing the function of the HMI as a storage device and a barcode scanner to retrieve the drug code to be stored in the HMI, using the drug code and drug name or keyword to search for drugs. With the time required for the system to search for drugs of less than 10 seconds, in this study the system has been able to make the drug data stored in the HMI system the same as the drug data on the machine.